PENGARUH PROSES HIDROTERMAL TERHADAP PENINGKATAN NILAI KALOR DAN PENURUNAN KADAR AIR PADA BATUBARA PERINGKAT RENDAH - Marlinda, Lenny; Pane, Xena Maharani; Wiratama, Jarot; Zahar, Wahyudi; Khadafi, Muhammad Reza; Rahmi (Indonesian Mining Journal, 2025)
As a low-rank coal, brown coal is characterized to have high water content. It is required a method to improve coal quality that can be used for effective coal utilization. One of the methods is to apply thermal dewatering technology which focuses on improving the quality of low-rank coal using water medium and autoclave. The purpose of this study was to determine the effect of coal to water ratio (w/v) and the effect of particle size of a low rank-coal on water content and calorific value using the hydrothermal method. Coal was processed under hydrothermal conditions at 150 °C for 60 min. For a mixture of 100 g of 25 mesh coal and 50 mL of water, the calorific value and water content after the hydrothermal process reached 5,849 kcal/kg and 5.10% (adb), respectively. While for a mixture of 100 g of 40 mesh coal and 50 mL of water, the calorific value and water content after the hydrothermal process reached 5,789 kcal/kg and 4.94% (adb), respectively. The calorific value obtained increased from the initial value of 3,296 kcal/kg and the water content decreased from the initial value of 44.34% for the coal condition before hydrothermal process. It can be concluded that the hydrothermal process with heating without oxygen carried out by a hydrothermal reactor could increase the calorific value of low-rank coal and reduce water content.